Asymmetric total synthesis of four bioactive lignans using donor–acceptor cyclopropanes and bioassay of (−)- and (+)-niranthin against hepatitis B and influenza viruses. Issue 8 (7th February 2022) - Ota, Ryotaro; Karasawa, Daichi; Oshima, Mizuki; Watashi, Koichi; Shimasaki, Noriko; Nishii, Yoshinori
Abstract : The total synthesis of four lignans including (−)- and (+)-niranthin has been achieved utilizing cyclopropanes. Based on bioassays of the (+)- and (−)-niranthins using HBV and IFV, we speculated the bioactive site of niranthin against HBV and IFV. Abstract : The asymmetric total synthesis of four lignans, dimethylmatairesinol, matairesinol, (−)-niranthin, and (+)-niranthin has been achieved using reductive ring-opening of cyclopropanes. Moreover, we performed bioassays of the synthesized (+)- and (−)-niranthins using hepatitis B and influenza viruses, which revealed the relationship between the enantiomeric structure and the anti-viral activity of niranthin.